Computational Models of Financial Price Prediction: A Survey of Neural Networks, Kernel Machines and Evolutionary Computation Approaches - Javier Sandoval (Ingeniería, 2011)
A review of the representative models of machine learning research applied to the foreign exchange rate and stock price prediction problem is conducted.  The article is organized as follows: The first section provides a context on the definitions and importance of foreign exchange rate and stock markets.  The second section reviews machine learning models for financial prediction focusing on neural networks, SVM and evolutionary methods. Lastly, the third section draws some conclusions.